Lyrical urban pictures of the New Objectivity - Brylla, Wolfgang (Acta Universitatis Lodziensis. Folia Germanica, 2020)
For the New Objectivity art, both literature and paintings, urban reality played a significant role. The aesthetics of the New Objectivity, movement that bloomed in the 20s and 30s, was defined through urban issues. This tendency can be observed primarily in the so-called Zeitroman that became a topic of interest for German literary studies earlier. In contrast to the prose, the New Objectivity poetry was rarely an object of studies. In the article, selected urban verses are analysed and connected with the New Objectivity paintings on a modernist background.